The Finest menswear in the world the craftsmanship luxury ; with 350 illustrations - Crompton, Simon (London Thames & Hudson, 2015)
The first menswear book to go in search of the finest clothes, accessories, and brands in the world, and to explain the craft which makes them the best of the best. With impeccable taste and an unerring eye for quality, connoisseur Simon Crompton seeks out the world’s most beautifully crafted contemporary menswear, item by item, from the Panama hat to the Milanese buttonhole. In profiles of fourteen distinguished companies that design, make, and sell their own products, Crompton tells the story of how each luxury item is crafted, explaining the subtle but crucial difference a hand-stitched seam, perfectly cut sleeve, or screen-printed silk can make. Augmented by extensive, specially commissioned photographs, The Finest Menswear in the World delves into every element of the well-dressed man’s wardrobe, both business and casual, from shirts to shoes, suits to scarves, and bags to umbrellas. With Crompton’s expert guidance, the discerning gentleman can dress himself head to toe in the finest menswear in the world. --Provided by publisher.
Keywords: Men's clothing